(untitled) (Dialogos, 2017)
Este artigo tem como propósito discutir algumas questões proeminentes do debate recente sobre o gênero biográfico, como os modos pelos quais os biógrafos produzem o enquadramento dos personagens e as tensões entre as dimensões ficcional e factual. Para trilhar este caminho, a opção escolhida foi a de recuperar, na forma de uma releitura, as escolhas e impasses que envolveram o percurso de minha tese de doutorado, na qual investiguei a trajetória intelectual do general Edmundo de Macedo Soares Abstract Re-encountering the General. Re-reading a doctoral thesis, nine years late This article aims to discuss some outstanding questions of the recent debate on the biographical genre, such as the ways in which the biographers produce the framing of the characters and the tensions between the fictional and factual dimensions. To cross this path, I chose to return, in the form of a re-reading, to the choices and dilemmas surrounding the route of my doctoral thesis, in which I investigated the intellectual trajectory of General Edmundo de Macedo Soares